Ceritinib in ROS1-positive non-small cell lung cancer patients: does clinical evidence carry clinical impact? - Facchinetti, Francesco; Tiseo, Marcello (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
Novel targets have recently joined EGFR and ALK as activating alterations suitable of specific inhibition, generating profound and durable clinical responses in non-small cell lung cancer (NSCLC) driven by these molecular alterations. These additional targets benefit from the experiences maturated in the setting of lung malignancies, with MET and ROS1 in particular, biologically similar to ALK and therefore being inhibited by shared compounds (1,2). Other molecular strategies of treatment take advantage of results obtained in different diseases, with the most relevant example represented by BRAF-mutated tumors (3) and NSCLC harboring HER-2 alterations (4), finding in melanoma and breast cancer their reference models, respectively.